Bovine Circadian Locomotor Output Cycles Kaput (CLOCK) and Clusterin (CLU) mRNA Quantitation in Ejaculated Crossbred Bull Spermatozoa. Issue 3 (6th April 2015) - Kumar, S; Deb, R; Singh, U; Ganguly, I; Mandal, DK; Tyagi, S; Kumar, M; Sengar, G; Sharma, S; Singh, R; Singh, R
Contents: Mammalian circadian locomotor output cycles kaput (CLOCK) gene encodes a transcription factor that affects both the persistence and the period of circadian rhythms. Earlier reports suggested that CLOCK gene might be associated with male infertility in human. Present investigation, for the first time, reports that CLOCK gene expresses differentially between good and poor quality crossbred bull semen. The relative expression of CLOCK was significantly (p < 0.05) higher among good quality bull semen than motility‐impaired ones. Clusterins (CLU) are series of genes associated with a variety of physiological activities including spermatogenesis, apoptosis and degenerative disease conditions. In the present context, we also investigated that the expression of CLU gene was significantly (p < 0.05) higher among motility‐impaired crossbred bull semen compared to the good quality one.